Diskriminasi Sosial dalam Novel Rasina karya Iksaka Banu - Putra, Ferro Oktawan; Adek, Muhammad (Persona: Kajian Bahasa dan Sastra, 2024)
This study endeavors to provide an academic account of the social class division depicted in the novel Rasina by Iksaka Banu, as well as an analysis of the portrayal of social discrimination and its implications in the narrative. The primary focus of this research is the novel Rasina, authored by Iksaka Banu and published in 2023. The research employs a descriptive literary research methodology, scrutinizing the words, phrases, clauses, and sentences pertaining to social class, discrimination, and the characters' dialogue and actions within the novel. The data collection technique employed encompasses reading and comprehending the novel, recording the pertinent data, and organizing it based on the research inquiries. The data analysis comprises several stages: (1) identifying data pertinent to social classes, discrimination, and its impact within the novel, (2) analyzing the accumulated data, and (3) presenting conclusions concerning the issue of social discrimination in a thesis format. The findings of this study disclose the various strata of social classes in Rasina, encompassing the bourgeoisie, petty bourgeoisie, middle class, labor aristocracy, proletariat, and lumpenproletariat. Furthermore, the study identifies two manifestations of social discrimination in the novel: direct and indirect. Lastly, the research examines the physical and psychological repercussions of social discrimination in Rasina.